Volunteer Participation in the Health eHeart Study: A Comparison with the US Population - Guo, Xiaofan (Sci Rep, 2017)
Direct volunteer “eCohort” recruitment can be an efficient way of recruiting large numbers of participants, but there is potential for volunteer bias. We compared self-selected participants in the Health eHeart Study to participants in the National Health And Nutrition Examination Survey (NHANES) 2013–14, a cross-sectional survey of the US population. Compared with the US population (represented by 5,769 NHANES participants), the 12,280 Health eHeart participants with complete survey data were more likely to be female (adjusted odds ratio (ORadj) = 3.1; 95% confidence interval (CI) 2.9–3.5); less likely to be Black, Hispanic, or Asian versus White/non-Hispanic (ORadj’s = 0.4–0.6, p < 0.01); more likely to be college-educated (ORadj = 15.8 (13–19) versus ≤high school); more likely to have cardiovascular diseases and risk factors (ORadj’s = 1.1–2.8, p < 0.05) except diabetes (ORadj = 0.8 (0.7–0.9); more likely to be in excellent general health (ORadj = 0.6 (0.5–0.8) for “Good” versus “Excellent”); and less likely to be current smokers (ORadj = 0.3 (0.3–0.4)). While most self-selection patterns held for Health eHeart users of Bluetooth blood pressure cuff technology, there were some striking differences; for example, the gender ratio was reversed (ORadj = 0.6 (0.4–0.7) for female gender). Volunteer participation in this cardiovascular health-focused eCohort was not uniform among US adults nor for different components of the study.